PENGARUH DEFFERED TAX DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE DENGAN PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2019 – 2023 - Ni Putu Dian Hartini; Made Yudi Darmita; Luh Gede Putri Kusuma Pekerti (UNHI Press, 2026)
Abstract: The Effect of Deferred Tax and Transfer Pricing on Tax Avoidance with Profitability as a Moderating Variable. This study aims to examine the effect of deferred tax and transfer pricing on tax avoidance, with profitability as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange during 2020–2023. This research employs a quantitative approach using secondary data obtained from annual financial reports. The sample consists of 33 companies selected through purposive sampling, resulting in 112 observations. Data analysis is conducted using descriptive statistics, classical assumption tests, and Moderated Regression Analysis (MRA). The results indicate that deferred tax has a positive and significant effect on tax avoidance, while transfer pricing has no significant effect. Furthermore, profitability strengthens the relationship between deferred tax and tax avoidance but does not moderate the relationship between transfer pricing and tax avoidance. These findings suggest that deferred tax plays a crucial role in corporate tax planning strategies, while transfer pricing is not directly associated with tax avoidance practices in the observed companies.